Understanding the Parable of the Good Samaritan: HOTS Dimensions - Tari, Ezra; Alexander, Ferdinant; Liufeto, Martin Chrisani; Tobing, Oscard Lumban (CV. AFDIFAL MAJU BERKAH, 2024)
It is critical to comprehend religious precepts that promote tolerance in light of the world's growing religious and societal divisions. The biblical tale of the Good Samaritan is frequently used as an example of moral principles and intergroup empathy. This study attempts to identify the ways in which a more profound comprehension of this fable might promote interfaith tolerance, particularly in a multicultural society. The methodology used in this study consists of a content analysis of the biblical text together with a survey of the literature on theology and sociology that is relevant to understanding the tale. Drawing upon the theoretical frameworks of interfaith discourse and social tolerance, the research highlights the need of valuing diversity in order to foster peaceful cohabitation. The results of the study show that, despite variations in religion or ethnicity, the Good Samaritan narrative offers a universal message of compassion and assistance. The narrative demonstrates the ability of humanitarian action to cut over social divides and ideological differences, which is critical in resolving conflicts in today's multicultural society. The study's main argument is that, in the context of religious diversity, a thorough comprehension of this fable may serve as a strong basis for encouraging interfaith communication and decreasing prejudices while also fostering tolerance.